Improving profitability in the Western Rocklobster Fishery using a rock lobster trap - Winzer, A.; Melville-Smith, Roy; de Lestang, S.; Thomson, A. (Seafood CRC, 2011)
This project commenced in the 2008/09 season and at that time the Western Rocklobster fishery was managed by input controls. The motivation for this study was that it was realised that a more efficient pot would reduce the number of pot hauls, and that this in turn would increase profitability of the fishery by reducing the amount of bait used, the amount of time at sea, fuel usage and overall wear and tear on equipment.